Evaluating the Quality of Light Emitted by Smartphone Displays - Nina Piechota; Krzysztof Skarżyński; Kamil Kubiak (Applied Sciences)
The increased use of smartphones in daily life challenges researchers regarding the quality of light emitted by screens. This study aims to analyze displays’ qualitative and quantitative light parameters from various smartphone models available on the market over the last decade. Advanced photometric and colorimetric measurements using complex instrumentation were performed. It covered the color gamut, channel linearity response, refresh rate, flickering, spatial radiation distribution, luminance, uniformity, and static contrast. The analysis showed that, despite advances in smartphone display technology, differences in visible radiation parameters between older and newer models are surprisingly marginal. However, improvements were observed in newer models in terms of viewing angles and compliance with the sRGB standard. Tested built-in blue light reduction filters were ineffective. It only slightly reduces light between 380 nm and 480 nm. In contrast, much higher decreases in this spectral range were achieved for dedicated applications. However, it lowered radiant power density across the visible spectrum, significantly decreasing the displays’ correlated color temperature. Enabling the power-saving mode caused the deterioration of parameters such as refresh rate, but the flicker depth remained constant. Static contrast for most tested devices was also at the same level. The findings confirm the need for further studies on display technology development that supports user well-being while minimizing its harmful effects.